PENGARUH PENJUALAN TUNAI, PENJUALAN KREDIT, DAN PENETAPAN HARGA TERHADAP LABA PENJUALAN PRODUK PIPA SET HD INVERTER 1 PK PADA PT. SUMBER MANDIRI CABANG KENJERAN SURABAYA - Anggraeni, Riris Mega Hardi (JEM17: Jurnal Ekonomi Manajemen, 2018)
PT. Sumber Mandiri Branch Kenjeran Surabaya is one of the distributor company of Spare Part Cooler one of its product is Pipe Set HD Inverter 1 pk. The purpose of this study is to determine whether there is influence of Sales Cash Sales Credit and Pricing on Sales Income Pipe Products Set HD Inverter 1 pk at PT. Sumber Mandiri Kenjeran Branch Surabaya. This type of research is quantitative research using secondary data obtained from PT Sumber Mandiri Kenjeran Branch Surabaya. Data analysis technique in this research is by using multiple regression analysis. This research is backed by technological advancement to encourage the development of cooling spare parts business that is increasing rapidly. To be able to survive the sales outlets refrigerated spare parts are required to maintain sales, both cash sales and credit sales. In keeping with the sale, the refrigerated spare parts sales outlet must have a marketing strategy, sales strategy, pricing strategy. The purpose of using the marketing concept is to improve relationships with customers because a better relationship can lead to sales and increase sales profit. The results of this study indicate that there are partial and simultaneous influence of variable Cash Sales (PT), Sales Credit (PK) and Pricing (PH) on Sales Income (LP) .There is partial influence of variable Cash Sales (PT), Credit Sales (PK) and Pricing (PH) on Sales Income (LP). Because the significance value in the t test of each variable indicates less than 0.05 is proven true and is accepted. There is influence simultaneously variable of Cash Sales (PT), Credit Sales (PK) and Price Pricing (PH) on Sales Profit (LP) Because the value of significance at test f shows smaller than 0.05 proved true and accepted. Sales income is explained by Cash Sales (PT), Credit Sales (PK) and Pricing (PH) of 0.997 or 99.7%. While the remaining 0.3% influenced by other variables outside the model in the perusal.Kata Kunci : Cash Sales, Credit Sales, Pricing, Sales Profi.